Mucocutaneous infections in HIV positive patients attending a tertiary care institution: a descriptive study - Haridas, Neethu; Muhammed, Kunnummal; S., Sarita (International Journal of Research in Dermatology, 2017)
Background: AIDS is characterized by the waning of body’s immunity leaving the victim to the multitude of life threatening opportunistic infections, neurological disorders or malignancies. Dermatologic manifestations occur in more than 90% of patients with HIV infection most often due to infections. The awareness of the varied patterns of these skin lesions would help in early diagnosis and management of these in HIV infection, which in turn reduce the morbidity and improve quality of life. Methods: Observational study from 1st April 2012 to 31st March 2013 in a tertiary care institution of North Kerala. HIV positive patients attending sexually transmitted infection clinic of Dermato venereology department, anti-retroviral treatment clinic (ART clinic) and infectious diseases ward of Department of Medicine of a tertiary care centre were examined after consent for mucocutaneous infections. Results: The study population comprised of 206 HIV infected patients with mucocutaneous infections. The male to female ratio was 2.07:1. Most of the affected belong to 30-50 years age group. Majority were manual laborers(49.3%) and in stage3 HIV disease. 107 patients had CD4 Count below 350 at the time of study(51.9%) whereas 40 cases (19.4%) had CD4Count above 500. Most common mucocutaneous infection was oral candidiasis (51%), followed by onychomycosis (16.5%). Out of 29 patients with dermatophytosis majority had tinea cruris (18 patients). Bacterial was second commonest infection. Only 3 patients had tuberculoid leprosy, one with type 1 reaction. Common viral infection was herpes zoster followed by herpes genitalis and conyloma accuminata. 11 patients had verruca vulgaris, one with extensive lesions. Out of 206 patients 28 had sexually transmitted infections (STIs) other than HIV, herpes genitalis being the commonest. Syphilis observed in 4 patients (1.9%). 162 patients (78.6%) were on HAART. The response to treatment was better in patients with CD4 Count above 500cells/mm3. Conclusions:Oral candidiasis, onychomycosis, pyoderma and ulcerative STIs were noted in significant number of HIV infected individuals. These were more common in those with CD4Count below 300 cells/ mm3. .Those patients with CD4 Count above 500 cells/ mm3 responded well to treatment.